Evidence on existing caries risk assessment systems: Are they predictive of future caries? (2013)
To critically appraise evidence for the prediction of caries using four caries risk assessment (CRA) systems/guidelines (Cariogram, Caries Management by Risk Assessment (CAMBRA), American Dental Association (ADA), and American Academy of Pediatric Dentistry (AAPD)). This review focused on prospective cohort studies or randomized controlled trials. A systematic search strategy was developed to locate papers published in Medline Ovid and Cochrane databases. The search identified 539 scientific reports, and after title and abstract review, 137 were selected for full review and 14 met the following inclusion criteria: (i) used as validating criterion caries incidence/increment, (ii) involved human subjects and natural carious lesions, and (iii) published in peer‐reviewed journals. In addition, papers were excluded if they met one or more of the following criteria: (i) incomplete description of sample selection, outcomes, or small sample size and (ii) not meeting the criteria for best evidence under the prognosis category of the Oxford Centre for Evidence‐Based Medicine. There are wide variations among the systems in terms of definitions of caries risk categories, type and number of risk factors/markers, and disease indicators. The Cariogram combined sensitivity and specificity for predicting caries in permanent dentition ranges from 110 to 139 and is the only system for which prospective studies have been conducted to assess its validity. The Cariogram had limited prediction utility in preschool children, and a moderate to good performance for sorting out elderly individuals into caries risk groups. One retrospective analysis on CAMBRA's CRA reported higher incidence of cavitated lesions among those assessed as extreme‐risk patients when compared with those at low risk. The evidence on the validity for existing systems for CRA is limited. It is unknown if the identification of high‐risk individuals can lead to more effective long‐term patient management that prevents caries initiation and arrests or reverses the progression of lesions. There is an urgent need to develop valid and reliable methods for caries risk assessment that are based on best evidence for prediction and disease management rather than opinions of experts.